GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA PENGARUHNYA TERHADAP KOMITMEN ORGANISASIONAL - Widyanti, Rahmi; Basuki, Basuki; Ratnasari, Sri Langgeng (Universitas Riau Kepulauan, 2021)
Focused on this research on the discussion of transformational leadership variables and job satisfaction that affect the organizational commitment of employees at PT. Global Makara Teknik Site BRE Banjarbaru Branch, South Kalimantan. The sample used in this study were 32 respondents who were saturated samples. The collected data from respondents used is a questionnaire to minimize differences in interpretation between respondents and researchers. Furthermore, this research used is the structural equation modeling (SEM) with theoretical and conceptual foundation, from the SEM-PLS program package so that the results are accurate. This result research found that transformational leadership style has a significant direct effect on employees of job satisfaction and organizational commitment. This proves that a good leadership style can provide job satisfaction to employees and increase organizational commitment.